Transhumanism vs. Theistic Ethics - Di Ceglie, Roberto (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
I argue that there are three limits to the transhumanist project of moral enhancement. They are “technological ignorance,” “technological passivity” and “technological easiness.” I argue that they make it unlikely that the enhancement in question will be achieved. I also argue that there are no similar limits in the context of theistic Christian ethics, although it may seem otherwise at first sight. Following Aquinas, I show that there is no “theological ignorance,” “theological passivity” or “theological easiness” that may hinder moral progress via the Christian faith. In conclusion, Christian theistic ethics is more beneficial to us than transhumanist views of moral enhancement.